Uṣā abhilāṣa (citrapothi) : = Uṣābhilāṣa = Usha abhilasha (chitrapothi) - Śiśuśaṅkara Dāsa (Orissa State Museum, 2010)
About Usha and Aniruddha; includes fragmentary reproduction of an 18th century illustrated manuscript preserved in the Orissa State Museum, Bhubaneswar, which depicts a variety of themes and situation; with critical introduction